AD, Volume 18, n° 3, 1993 - Full Issue - Journal System, (Africa Development, 2022)
Contents The Changing Pattern of Private Foreign Investments in the Nigerian Oil Industry Kayode Soremekun & Cyril Obi .......................... 5 Les nouvelles relations Est-Ouest et leurs incidences sur la coopération CEE-ACP Blaise Sary Ngoy ................................ 21 Public Control and Public Enterprise Performance in Sub-Saharan Africa: The Case of Tanzania and Zambia J Wagona Makob .................................... 37 La politique industrielle: controverses et démarche stratégique en Afrique au Sud du Sahara: le cas du Sénégal Seck Alioune .................................... 61 Les initiatives féminines au Sénégal: une réponse à la crise? Fatou Sow ................................ 89 The State and the Market: Reflections on Ake's Analysis of the Stale in the Periphery O. Okechukwu Ibeanu ........................ 117 Book Reviews Continuity and Change in Nigerian Foreign Policy by Paul P Izah (Ahmadu Bello University Press) 1991, 153 pp John Amfani Ayam ........................ 133 René Collignon et Charles Becker - Santé et population en Sénégambie des origines à I960. Biblographie annotée Paris: INED, 1989, 554 p Momar Coumba Diop .................... 136 Publications Received ..............................139